5.17 REGARDING EDUCATION OF STUDENTS IN THE SPIRIT OF NATURE PROTECTION - Khamrayeva Guli Nurmakhmatovna Teacher of Samarkand State Medical University xamrayevaguli50@gamil.com Eshquvvatova Shahnoza Dilmurod qizi Student of Samarkand State Medical University (Innovative technologies in construction Scientific Journal, 2024)
Annotation: Along with the reform of the education system in the Republic of Uzbekistan, the use of modern educational methods in instilling environmental knowledge in students has always remained relevant. From this point of view, in the article we tried to highlight the problems of nature conservation and environmental education of university students Keywords: nature protection, health improvement, beautification, pedagogical thought, nature conservation, natural science. Acquainting children with nature is of great importance in the development of the young generation in all aspects. When educating young people, first of all, we should explain the significance and necessity of education both for our society and for the formation of a person on a scientific basis. In general education, we should use the materialistic point of view on the elements of nature, its riches, animate and inanimate nature, and teach young people to fully understand its secrets, learn and use them wisely. In fact, all-round formation of a person takes place only in our society. Because mother nature is always open for young people to grow and mature.